"Credit Power and Democracy," by Major C. H. Douglas, considered - Leet, Francis L. (Statistical and Social Inquiry Society of Ireland, 1925)
Bishop Berkeley had the reputation in his own day of having written a book?The Principles of Human Knowledge? which no one could understand. 'His labours', said a contemporary philosopher of some eminence, 'are of little use on account of their abstruseness.' Yet Berkeley believed that by means of that book he had 'done away with the chief causes of error and difficulty in the sciences.' I am proposing now to attempt some examination of that remarkable book, Credit Power and Democracy, written, together with some other works of a kindred nature, by Major C. H. Douglas.
Read Friday, 12th December, 1924
Keywords: Douglas, C.H.; Egalitarianism; Credit power and democracy; 314.15